2005
DOI: 10.1002/hep.20857
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Function of L-FABP in L-FABP Stably Transfected Chang Liver Cells *

Abstract: C ellular oxidative stress is one of the factors responsible for the propagation of liver diseases, such as hepatitis, cirrhosis, and hepatoma. 1 Several primary antioxidant defense systems such as superoxide dismutase (SOD), catalase, glutathione (GSH), and glutathione peroxidase are present intracellularly. These systems scavenge reactive oxygen species (ROS) such as hydrogen peroxide, superoxide, lipid peroxides, and free radicals. Exposure to oxidative stress may, however, deplete the cellular antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(114 citation statements)
references
References 49 publications
(43 reference statements)
4
109
0
1
Order By: Relevance
“…In the liver of LPS/D-GalNtreated mice, numerous apoptotic cells were detected by TUNEL assay ( Figure 2E), while in animals treated with D-glucose, the staining for apoptotic nuclei is negative ( Figure 2F). Analysis of two markers of liver injury, ie, ALT and LDH 11,12 in the sera of the different groups of mice, measured 6 hours after LPS/D-GalN administration, further confirmed the protective effect of D-glucose; in fact, the strong increase of plasma ALT and LDH levels observed after LPS/D-GalN administration was significantly reduced in D-glucose pretreated mice (ALT: During LPS/D-GalN intoxication, ICAM-1 expression in hepatocytes and nonparenchymal cells is enhanced. Upregulation of this molecule is necessary for extravasation, into the liver parenchyma, of neutrophils, which produce cytotoxic damage to hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In the liver of LPS/D-GalNtreated mice, numerous apoptotic cells were detected by TUNEL assay ( Figure 2E), while in animals treated with D-glucose, the staining for apoptotic nuclei is negative ( Figure 2F). Analysis of two markers of liver injury, ie, ALT and LDH 11,12 in the sera of the different groups of mice, measured 6 hours after LPS/D-GalN administration, further confirmed the protective effect of D-glucose; in fact, the strong increase of plasma ALT and LDH levels observed after LPS/D-GalN administration was significantly reduced in D-glucose pretreated mice (ALT: During LPS/D-GalN intoxication, ICAM-1 expression in hepatocytes and nonparenchymal cells is enhanced. Upregulation of this molecule is necessary for extravasation, into the liver parenchyma, of neutrophils, which produce cytotoxic damage to hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of FABP1 in mutant mice causes problem in branched-chain fatty acid metabolism [41]. A recent study showed the antioxidant function of FABP1, and increased expression of FABP1 in a liver cell line reduced cellular damage from hypoxia/reoxygenation [42]. Therefore, similar to CAIII deficiency, reduced FABP1 may contribute to a further increase in oxidative damage in Sod1−/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…24 Briefly, 2,7-dichlorofluorescein diacetate (DCFH-DA, Molecular Probes Inc., Eugene, OR, USA) was applied to the culture medium after exposure to EGCG at various concentrations or other reagents. Fluorescent units were measured in each well after 45-min incubation with DCF (5 mM) with excitation wavelength of 485 nm and emission wavelength of 530 nm using a fluorescence multiwell plate reader (Genios Plus, Tecan, San Jose, CA, USA).…”
Section: Determination Of the Level Of Cellular Rosmentioning
confidence: 99%